The power economy : building an economy that works - Wilson, John Oliver (Boston : Little, Brown, 1985)
This book shows strong-willed and idealistic political leaders who came to power at a unique turning point of history
Includes index.
Includes bibliographical references: p. 291-294.
mf 21/01/2019
Loans
Keywords: Economic policy; United States; Great Britain; France; Germany (West); Japan